Mosaic blood vessels in tumors: Frequency of cancer cells in contact with flowing blood - Chang, Yong S. (The National Academy of Sciences, 2000)
The presence of “mosaic” vessels in which both endothelial cells and tumor cells form the luminal surface has profound implications for metastasis, drug delivery, and antivascular therapy. Yet little is known of the frequency, and thus importance, of mosaic vessels in tumors. Using CD31 and CD105 to identify endothelial cells and endogenous green fluorescent protein labeling of tumor cells, we show that ≈15% of perfused vessels of a colon carcinoma xenografted at two different sites in mice were mosaic vessels having focal regions where no CD31/CD105 immunoreactivity was detected and tumor cells appeared to contact the vessel lumen. These regions occupied ≈25% of the perimeter of the mosaic vessels, or ≈4% of the total vascular surface area in these colon carcinomas. In addition, we found similar numbers of mosaic vessels in human colon carcinoma biopsies. Our results are consistent with the observation that ≈10(6) cells are shed daily per g of tumor. More importantly, our data offer a possible explanation for the antivascular effects of cytotoxic agents and suggest potential strategies for targeting the tumor vasculature.